1999
DOI: 10.1094/phyto.1999.89.11.1038
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Tomato Yellow Leaf Curl Virus (TYLCV)-Sr by TYLCV-Is in Tomato Epidemics in Spain

Abstract: A progressive displacement of tomato yellow leaf curl virus (TYLCV)-Sr by TYLCV-Is was observed in tomato epidemics in southern Spain based on incidence data of both virus species obtained during surveys conducted between 1996 and 1998. Ecological factors that might be involved in such a displacement, such as competition of TYLCV-Sr and TYLCV-Is in tomato, transmission by local biotypes (B and Q) of Bemisia tabaci, and presence in weeds and alternate crops, have been analyzed. No selective advantage is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 22 publications
2
98
0
10
Order By: Relevance
“…the ability to be inoculated and to initiate an infection) is 37% higher for TYLCV-IL than for TYLCV-Mld. Epidemiological factors other than transmission rate, such as extended host range [7,34], might be involved in the shift of viral populations. However, as previously described in Florida [35], in Réunion Island TYLCV does not require alternative hosts during intercropping or overwintering periods, because tomato plants are cultivated all year long.…”
Section: Discussionmentioning
confidence: 99%
“…the ability to be inoculated and to initiate an infection) is 37% higher for TYLCV-IL than for TYLCV-Mld. Epidemiological factors other than transmission rate, such as extended host range [7,34], might be involved in the shift of viral populations. However, as previously described in Florida [35], in Réunion Island TYLCV does not require alternative hosts during intercropping or overwintering periods, because tomato plants are cultivated all year long.…”
Section: Discussionmentioning
confidence: 99%
“…Although no symptoms are observed in fruits, infected plants are less vigorous and produce fruits with reduced market value. In addition to tomato, some TYLCD-associated viruses also have been involved in infections of common bean (Phaseolus vulgaris L.) (Navas-Castillo et al, 1999) and pepper (Capsicum annuum L. and C. chilensis Jacq.) (Morilla et al, 2005;Polston et al, 2006) crops.…”
Section: The Tomato Yellow Leaf Curl Disease and Associated Virusesmentioning
confidence: 99%
“…The spread of TYLCD in Spain is well documented (Sánchez-Campos et al, 1999. The first reports of infections were of the early 1990's.…”
Section: The Tomato Yellow Leaf Curl Disease and Associated Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Muñiz (2000) and Nombela et al (2001) have reported differences between the host responses to B-and Q-biotypes of B. tabaci in common weeds (Datura stramonium L., Solanum nigrum, L., Brassica kaber (DC), Capsella bursa-pastoris L. and Malva parviflora L.) and tomato plants. Moreover, some differences in transmission efficiencies of the B. tabaci biotypes when transmitting TYLCV/TYLCSV from tomato to tomato have been already reported (Sánchez-Campos et al, 1999), but few experimental studies had been undertaken to date on the transmission of TYLCSV-ES (Sánchez-Campos et al, 2000). Therefore, the aim of the present study was to compare the transmission efficiency of TYLCSV-ES by the Spanish B-, Q-and S-biotypes of B. tabaci, from different common weeds to tomato plants and vice versa.…”
Section: Resumen Nota Corta Efecto Del Biotipo De Bemisia Tabaci En mentioning
confidence: 99%